Srednja relativna variabilnost padavin v Sloveniji v obdobju 1991–2020 - Čotar, Alen (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2024)
Given the considerable disparities in precipitation amounts in the various regions of Slovenia, the mean relative variability was used as an indicator of precipitation variability in the period 1991–2020. The annual variability analyzed for 174 precipitation stations ranges from 8 % to 18 %. The highest annual precipitation variability was observed in western and northwestern Slovenia. Seasonal variability was assessed for 37 representative stations. Winter precipitation exhibits the greatest variability, characterized by a mean relative variability of approximately 40 %, which is primarily due to fluctuations of the Mediterranean cyclogenesis. In the other seasons, the variability ranges from 20 % to 25 %.
Keywords: climate change; climatogeography; klimatogeografija; padavine; percipitation; percipitation variability; podnebne spremembe; Slovenia; Slovenija; variabilnost padavin